Effects of postbiotic metabolites produced by Lactobacillus plantarum and acidifier on weight and meat quality of broiler chickens - Mohd Radzi, Rosyidah (2015)
Postbiotic metabolite produced by Lactobacillus plantarum is intermediate and final metabolic product of bacteria. There have antibacterial effect from organic acids and bacteriocin. Acidifier known as feed additive to improve performance of broiler chicken. The studies investigate the synergistic effect of combination of postbiotic metabolite produced from L. plantarum strains with acidifier on broiler chicken. Three experiments were conducted to achieve the objectives. Experiment I was conducted to select the best combinations by determination of inhibitory activity assessment. Six strains of Lactobacillus plantarum (UL4, TL1, RS5, RI11, RG11 and RG14) and 0.1% until 0.5% concentrations of acidifiers (malic acid and citric acid) were used in this study. Seventy six of the postbiotic metabolite and acidifier treatment were produced. The inhibitory activity against Pediococcus acidilactici, Salmonella enterica, Escherichia coli and Listeria monocytogenes of UL4 combine with 0.5% malic acid, RG14 combine with 0.5% malic acid and TL1 combine with 0.4% citric acid showed higher score than the other treatments. Therefore, these treatments were selected for further studies. Experiment II was carried out to determine the effects of combinations postbiotic metabolite with acidifier on the growth performance, fecal pH,microflora counts, villi height and crypt depth. A total of 150 male Cobb broilers were raised for 42 days. The birds were randomly divided into 5 groups and fed with various treatment diets: (i) basal diet (control); (ii) basal diet supplemented with antibiotic (positive control) (iii) basal diet supplemented with 0.3% of UL4 + 0.5% malic acid (iv) basal diet supplemented with 0.3% of RG14 + 0.5% malic acid and (v) basal diet supplemented with 0.3% of TL1 + 0.4% citric acid. Feeding of combination postbiotic metabolites with acidifier and control group did not showed significant different (p>0.05) for growth performance and lactic acid bacteria counts. Enterobacteriocea (ENT) count result showed that UL4 + 0.5%MA and RG14+0.5%MA did not showed significant different (p>0.05) with positive control. Combination of RG14 + 0.5% MA showed better effect than control group for histopathology of small intestine. The results indicate that, the inclusion combination of postbiotic metabolite and acidifiers have shown potential effect similar to antibiotic diet group for growth performance, faecal pH,and lactic acid bacteria population. Besides that, it also reduced the population of Enterobacteriaceae and increase villus height of small intestine. Overall, combination of RG14 + 0.5% malic acid prominently shows improved effect as compared to other treated diets. Experiment III was carried out to determine the carcass composition and meat quality of chickens fed with combination of postbiotic metabolite with acidifier. This experiment was continued from second experiment. This study was conducted to examine the effects of feeding postbiotic metabolites which produced from L. plantarum and acidifier in the diets of broilers chickens on carcass composition and meat quality. Generally, combination UL4 + 0.5% MA and RG14 + 0.5% MA had shown similar effect as control group for carcass weight, meat percentage and meat quality traits. Nevertheless, the supplementation of combination postbiotic metabolites and acidifier significantly reduced (p<0.05) abdominal fat and increased (p<0.05) percentage of bone. Thus, these findings suggested that postbiotic metabolite produced by locally isolated L. plantarum combine with acidifier is potential alternative feed additives in poultry production.